Bacteriocinogeny in experimental pigs treated with indomethacin and Escherichia coli Nissle - Bures, Jan; Smajs, David; Kvetina, Jaroslav; Förstl, Miroslav; Smarda, Jan; Kohoutova, Darina; Kunes, Martin; Cyrany, Jiri; Tacheci, Ilja; Rejchrt, Stanislav; Lesna, Jirina; Vorisek, Viktor; et al. (World journal of gastroenterology, 2011)
AIM: To evaluate bacteriocinogeny in short-term high-dose indomethacin administration with or without probiotic Escherichia coli Nissle 1917 (EcN) in experimental pigs. METHODS: Twenty-four pigs entered the study: Group A (controls), Group B (probiotics alone), Group C (indomethacin alone) and Group D (probiotics and indomethacin). EcN (3.5×10(10) bacteria/d for 14 d) and/or indomethacin (15 mg/kg per day for 10 d) were administrated orally. Anal smears before and smears from the small and large intestine were taken from all animals. Bacteriocin production was determined with 6 different indicator strains; all strains were polymerase chain reaction tested for the presence of 29 individual bacteriocin-encoding determinants. RESULTS: The general microbiota profile was rather uniform in all animals but there was a broad diversity in coliform bacteria (parallel genotypes A, B1, B2 and D found). In total, 637 bacterial strains were tested, mostly Escherichia coli (E. coli). There was a higher incidence of non-E. coli strains among samples taken from the jejunum and ileum compared to that of the colon and rectum indicating predominance of E. coli strains in the large intestine. Bacteriocinogeny was found in 24/77 (31%) before and in 155/560 (28%) isolated bacteria at the end of the study. Altogether, 13 individual bacteriocin types (out of 29 tested) were identified among investigated strains. Incidence of four E. coli genotypes was equally distributed in all groups of E. coli strains, with majority of genotype A (ranging from 81% to 88%). The following types of bacteriocins were most commonly revealed: colicins Ia/Ib (44%), microcin V (18%), colicin E1 (16%) and microcin H47 (6%). There was a difference in bacteriocinogeny between control group A (52/149, 35%) and groups with treatment at the end of the study: B: 31/122 (25%, P=0.120); C: 43/155 (28%, P=0.222); D: 29/134 (22%, P=0.020). There was a significantly lower prevalence of colicin Ib, microcins H47 and V (probiotics group, P<0.001), colicin E1 and microcin H47 (indomethacin group, P<0.001) and microcins H47 and V (probiotics and indomethacin group, P=0.025) compared to controls. Escherichia fergusonii (E. fergusonii) was identified in 6 animals (6/11 isolates from the rectum). One strain was non-colicinogenic, while all other strains of E. fergusonii solely produced colicin E1. All animals started and remained methanogenic despite the fact that EcN is a substantial hydrogen producer. There was an increase in breath methane (after the treatment) in 5/6 pigs from the indomethacin group (C). CONCLUSION: EcN did not exert long-term liveability in the porcine intestine. All experimental pigs remained methanogenic. Indomethacin and EcN administered together might produce the worst impact on bacteriocinogeny.
Keywords: Sus scrofa; metagenom; Escherichia coli Nissle 1917; Bacteriocinogeny; dechové testy; probiotika; Indomethacin; střevní sliznice; Escherichia coli; methan; Breath Tests; Methane; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; bakteriociny; Bacteriocins; Metagenome; Animals; lidé; ženské pohlaví; Humans; zvířata; Intestinal Mucosa; Experimental pigs; Probiotics; indomethacin; Female